Point de vue d’un acteur français sur la controverse des pluies acides (1983-1991) - Gabrielle Bouleau (VertigO, 2016)
This paper is based on an interview with Christian Barthod, member of the Corps at Ponts, des Eaux et des Forêts (France), presently employed at Conseil général de l’environnement et du développement durable (CGEDD). Member of the Académie d’agriculture (Wood and Forests section), Christian Barthod was the head of the Research and Technology Office (1983 to 1988) and the Forest Health Department (1988 to 1995) at direction des forêts. At such, he was involved in the controversy in France and Europe around impacts of acid rain (Arnould et Da Lage 1993, Hajer 1993, Roqueplo 1993). The aim of this interview is to highlight the national and international debate on the ecological modernization that is going on in Germany, Holland, but not in France.